(untitled) (Journal Edutama Multidisciplinary Indonesian, 2024)
The position of religious courts has a strong position in terms of authority, because it has been aligned with other courts in the highest regulations in the hierarchy of legislation. Religious Courts are one of the judicial bodies that enforce law and justice for the people of justice in certain cases between Muslims in the fields of Marriage, inheritance, wills, grants, waqf, zakat, infaq, sadaqah, and Islamic economics that all court decisions and decisions must contain certain articles in laws and regulations or unwritten legal sources that are used as the basis for judging. From the contents of the article, it can be concluded that unwritten law can be used as a basis in religious courts to make decisions. If the article is not limited, then not only Islamic law can be applied as the basis for making decisions, but also includes other provisions that exist in social relations, for example customary law in inheritance matters which are indeed a phenomenon in society